Evidential marking in European languages toward a unitary comparative account - Wiemer, Björn, 1966-; Marín Arrese, Juana I.; Carretero, Marta; Cid Abasolo, Karlos; Dendale, Patrick; Domínguez Romero, Elena; González Vázquez, Mercedes, 1969-; Letuchiy, Alexander; Martín de la Rosa, Victoria; Moraes Abrahão, Viviane de; Mortelmans, Tanja; Ruskan, Anna; et al. (Studia typologica ;, 2022)
How are evidential functions distinguished by means other than grammatical paradigms, i.e. by function words and other lexical units? And how inventories of such means can be compared across languages (against an account also of grammatical means used to mark information source)? This book presents an attempt at supplying a comparative survey of such inventories by giving detailed "evidential profiles" for a large part of European languages: Continental Germanic, English, French, Basque, Russian, Polish, Lithuanian, Modern Greek, and Ibero-Romance languages, such as Catalan, Galician, Portuguese and Spanish. Each language is treated in a separate chapter, and their profiles are based on a largely unified set of concepts based on function and/or etymological provenance. The profiles are preceded by a chapter which clarifies the theoretical premises and methodological background for the format followed in the profiles. The concluding chapter presents a synthesis of findings from these profiles, including areal biases and the formulation of methodological problems that call for further research.